Sikap dan Persepsi Siswa dan Guru SMA Kota Jambi terhadap E-Learning dalam Pembelajaran IPA - M Alwi; Muhammad Damris; Rayandra Asyhar (Universitas Jambi, 2014)
This is a study of the attitudes and perceptions of students and teachers towards e-learning in some schools in the city of Jambi. Information in the form of knowledge attitudes and perceptions of students and teachers towards e-learning becomes an input for teachers in a lesson plan. With the approach combined methods of research sequential-explanatory model of the phase I study design using quantitative methods to answer the problem formulation, and phase II testing hypotheses using qualitative methods to establish, expand and deepen the results of quantitative research methods. The total population of 1,661 people, and 175 students are samples obtained by random and representative for purposive quantitative methods to qualitative methods, and teachers sampled 37 of the 48 people.Quantitative data collected through filling questionnaire and qualitative data by interview and observation, descriptive analysis results obtained variable values Student Attitudes (SS) = 78.3%, variables Student Perceptions (PS) = 78.4% and variable E-learning (EL) = 78.3% and each variable in both categories. For teacher sample of from descriptive analysis values variable Teacher Attitudes (SG) = 79.4%, variable Teacher Perceptions (PG) = 79.8% and variable EL = 78.7% and each variable in both categories. Overall attitudes and perceptions of students and teachers towards e-learning in science teaching is good.